2016
DOI: 10.1007/s11899-016-0302-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Manipulation With Prebiotics and Probiotics in Patients Undergoing Stem Cell Transplantation

Abstract: Hematopoietic stem cell transplantation (HSCT) is a potentially life-saving therapy that often comes at the cost of complications such as graft-versus-host disease and post-transplant infections. With improved technology to under-stand the ecosystem of microorganisms (viruses, bacteria, fungi, and microeukaryotes) that make up the gut microbiota, there is increasing evidence of the microbiota’s contribution to the development of post-transplant complications. Antibiotics have traditionally been the mainstay of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 99 publications
0
33
0
Order By: Relevance
“…The beneficial effects of enteral feeding may be related to the prebiotic properties of fiber from select fruits and vegetables . Prebiotics are indigestible carbohydrate that is fermented by colonic flora or commensals to produce short chain fatty acids (SCFAs) such as butyrate, acetate, and propionate that are utilized as an energy source by and promote the health of the human enterocyte .…”
Section: Intestinal Dysbiosis and Allogeneic Hsctmentioning
confidence: 99%
“…The beneficial effects of enteral feeding may be related to the prebiotic properties of fiber from select fruits and vegetables . Prebiotics are indigestible carbohydrate that is fermented by colonic flora or commensals to produce short chain fatty acids (SCFAs) such as butyrate, acetate, and propionate that are utilized as an energy source by and promote the health of the human enterocyte .…”
Section: Intestinal Dysbiosis and Allogeneic Hsctmentioning
confidence: 99%
“…Among these, Clostridium difficile is the most common. The emergence of the NAP1/027 strain of C. difficile over the first decade of the twenty-first century has been associated with more severe infection [11, 12]. Recent data reveal that C. difficile has surpassed Methicillin-resistant Staphylococcus Aureus (MRSA) to become the most prevalent nosocomial infection in community hospitals in certain regions of the United States [13].…”
Section: Main Textmentioning
confidence: 99%
“…Recent literature show CDI rates among SCT recipients are up to nine times higher than in the general inpatient population [11, 12]. A study by Jain et al found that 12 percent of patients admitted to their institution for SCT were colonized with toxigenic C. difficile [14].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylactic use of antibiotics has been to prevent the potential risk of infection postoperatively as pre-and perioperative antibiotics have been found to lower the infection rate [26]. To assist the recolonization of the microbiota, it is recommended to use pre-and probiotics [28].…”
Section: General Surgery Considerationsmentioning
confidence: 99%